Hubungan Pengetahuan dan Sikap Tenaga Kesehatan dengan Perilaku pemberian Teknik Relaksasi dan Teknik Distraksi pada Nyeri Pasien Pasca Operasi Sectio Caesarea di Rumah Sakit Baiturrahim - Yuliana Yuliana; Nikmatur Rohma (Jurnal Akademika Baiturrahim Jambi, 2021)
Sectio caesaria surgery can cause changes in the continuity of body tissues and the aftereffect of delivery of a caesarean section is that the patient will feel pain after 2 hours of operation to 3 days and the pain feels hot in the incision scar. Efforts to reduce pain intensity are using non-pharmacological pain management, namely distraction and relaxation techniques. This study used cross sectional approach by using description correlation design which conducted at Baiturrahim hospital Jambi city, sample were health personnel (Nurse and Midwife), the sampling technique used total sampling. The collecting of data used a questionnaire by using Chi-Square test. The findings indicated that from 21 respondents 13 (61.9%) respondents have sufficient knowledge of health personnel, 14 (71.4%) respondents have Positive attitude of health personnel, 20 (95.2%) respondents have good health personnel behavior in giving distraction and relaxation techniques to pain patients. From the result of chi square test indicated that score p-value 0.381 so that the null hypothesis is accepted, namely there is no correlation between knowledge of health personnel with the behavior of giving distraction and relaxation techniques in postoperative pain patients with sectio caesarea at Baiturrahim hospital. It is expected to Baiturrahim hospital in order to increase services in providing non-pharmacological techniques to reduce pain intensity in post-caesarean section patients